Beneficios del tratamiento fisioterapéutico en adultos con virus de inmunodeficiencia humana - Mayorga Olivo, Allison Nicole (2022)
ABSTRACT: The research was elaborate under a bibliographic modality review, with the objective of determining the benefits of physio therapeutic treatment in adults with the human immunodeficiency virus. The human immunodeficiency virus or HIV is a retrovirus which attacks cells preventing the proper functioning of the immune system, is currently estimated that 38 million of people are living with HIV around the world, however, the use of antiretrovirals allows this population to prolong their time of life, determining HIV as a chronic disease, which causes comorbidities or limiting affections from them. The type of research used in the present writing was documentary since it is based on the analysis of information from different sources such as scientific articles, theses, among others, collected from databases (PubMed, Scielo, Google Scholar, Elsevier, Ovids), whose information was selected from 35 articles, determined by inclusion and exclusion criteria, search strategies and assessment using the PEDro scale. The physio therapeutic treatment based mainly on aerobic and resistance physical training provides patients muscle enhancements, bony and decreased range of pain, among others, which form necessary components to carry out activities of daily life and improve the quality of life; therefore, physio therapeutic rehabilitation in this population is essential to reduce physical deterioration and promote the independence of patients.